Implementation of E-Government in Regions Study on Bombana Public Service Mall - Mardiana Mardiana; Murni Ratna Sari Alauddin (Jurnal Office, 2022)
The application of e-government into the  public service sector in the regions is the focus of this research. Electronic-based public services at the Bombana Regency Public Service Mall are the foundation of community expectations to get easy, fast, safe and comfortable access to services. such as service delays, extortion, nepotism and discrimination. Through research findings analyzed with an interactive data analysis model, it shows that the implementation of E-government at MPP Bombana has been based on electronic services by utilizing applications or websites as a medium of communication and information between the government and the community. In addition, the implementation of E-government at MPP Bombana has demonstrated the process of interaction and transactions between governments and service users with a website-based service system that makes it easy for the public to access the public information they need, manage licensing and non-licensing documents quickly, safely and comfortably.  However, MPP Bombana has not been able to develop its E-Government services to a transformational stage so that interconnectivity in an integrated online service system has not been realized.